Analisis Nilai Gizi Telur Itik Asin Yang Dibuat Dengan Media Kulit Buah Manggis Selama Masa Pemeraman (NUTRIENT ANALYSIS OF DUCK SALTED EGGS MADE BY MANGOSTEEN RIND MEDIA DURING SALTING PERIODS) - Agustina, Kadek Karang; Dharmayudha, Anak Agung Gde Oka; Swacita, Ida Bagus Ngurah; Sudimartini, Luh Made (Buletin Veteriner Udayana, 2015)
The purposes of this research were to determine the level of nutrient in duck salted eggs made by using mangosteen rind media observed by water content, ash, fat, protein and carbohydrate during salting periods. This research used Completely Randomized Design (CRD), with twofactors. First were media;   mangosteen rind media and brick media. Second were salting periods;7, 14 and 21 days. The level of nutrient contain in duck salted eggs measured according to  Association of Official Analytical Chemist (1984) methods. These data analyzed by T tests tocompare the level of nutrient contain in duck salted eggs produced between medias during saltingperiods. The results show that during the curing process by using the mangosteen rind media wasobserved at days 7, 14 and 21 decreased water and fat content of salted eggs. While the ash, proteinand carbohydrates content increased successively. When compared with the bricks media, all levelof nutritional parameters did not show a significant difference. So it can be concluded that themangosteen rind can be used as a media for making salted eggs.
Keywords: nutrient level; salted eggs; mangosteen rind